Stable and easily sintered BaCe0.5Zr0.3Y0.2O3-delta electrolytes using ZnO and Na2CO3additives for protonic oxide fuel cells - Li, Y.; Guo, R.; Wang, C.; Liu, Y.; Shao, Zongping; An, J.; Liu, C. (Pergamon, 2013)
BaCe0.5Zr0.3Y0.2O3-delta (BCZY) based composite electrolyte materials were fabricated with ZnO sintering aid (BCZY-Z). The effects of Na2CO3 modification on sintering behavior, chemical stability and electrochemical performance were systematically investigated. The X-ray diffraction patterns indicate that the specimens with Na2CO3 addition possessed a single perovskite structure after sintering at 1320 degrees Celcius for 2 h. The linear shrinkage of 0.5 mol% Na2CO3-modified BCZY-Z sample (BCZY-Z-C2) was about 17.5%, higher than that without Na2CO3 addition (14.9%). Energy dispersive spectrometer shows that Na and C elements still existed and mainly distributed along the grain boundaries. Reactivities with carbon dioxide and boiling water of BCZY-Z and Na2CO3-modified BCZY-Z samples were also evaluated and good chemical stability was observed for Na2CO3-modified BCZY-Z samples. A conductivity of 7.68 * 10-3 S cm-1 for BCZY-Z-C2 was obtained at 700 ?C in 3% wet hydrogen atmosphere. An anode-supported fuel cell with thin-film BCZY-Z-C2 as electrolyte was fabricated. The fuel cell delivered a peak power density of 302 mW cm2 and interface resistance value of 0.08 Ohm cm2 at 700 degrees Celcius.